Proposta de um fluxo para elaboração e implementação de planejamento estratégico em instituições públicas de ensino superior - Oliveira, Eduardo José de (2019)
The strategic planning process proposes to define the actions that organizations take to transform their goals into reality. Strategic planning is understood as an administrative process to enhance the degree of interaction with the environment, providing a differentiated and innovative action to follow a planning. Many models of strategic planning have been developed for private organizations, however, few of them have been adapted, combined or complemented for the specific characteristics of public organizations. Thus, the objective of this research is to develop a flow for the elaboration and implementation of strategic planning in public institutions of higher education. So, a review of the literature on strategic planning was done in order to identify the tools and methods for its construction. This research consists of a case study, by means of non-participant observation of the researcher. The data collection and the analysis were carried by the SWOT matrix, for the diagnosis of strengths, weaknesses, threats and opportunities and by the PESTEL analysis, it to understand how external change will affect the institution. It was made the projection of Scenarios for a better vision of the future for the case in study. In this regard, it was selected the adapted Canvas to structure the tactical details of implementation of each strategic action and finally the Scrum methodology for project management was adopted. As a result, it was developmented of a flow for the elaboration and implementation of the strategic planning that can applied at Campus Cornélio Procópio of the UTFPR. This fluxo resulted in the formulation of 80 actions divided into 8 strategic objectives planned to be implemented between 2018 and 2022. The project is in the implementation phase with actions already being implemented. The research made it possible to verify that strategic planning contributes to the definition of the most appropriate course for the university through the formulation of strategic actions to reach the goals and so that it can more efficiently and effectively improve the search performance for future desired situations. The developed flow can help other Campus of the UTFPR and public institutions of higher education, with characteristics similar to UTFPR, to elaborate their actions to compose their strategic planning.